(untitled) (International Educators Conference, 2025)
This article presents theoretical information on the use of time management technology in the process of students’ independent learning, alongside the current attention given to this area and the challenges that persist. The didactic possibilities of applying time management strategies to enhance students’ competence in independent learning are analyzed from a scientific perspective.